Development status of indigenous computational fluid dynamics software for arbitrary complex geometry - Ng, Khai Ching; Mohd Zambri, Yusoff, Dr.; Talal, Yusaf, Dr.; I., Hussein (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/